To Create a Hero: Nationalism narrative in Cüneyt Arkin's historical film series - Nizam, Feridun; Kan, Seher (IGI Global, 2023)
In this study, the representations of the "nationalist-conservative" ideology in Turkish cinema are analysed through the mixed methods of narrative historical criticism and actor analysis with the sample of historical film series. Among the nationalist-conservative films with a considerable universe size, Kara Murat, Malkoçoğlu, and Battalgazi film series in which Cüneyt Arkin is the leading actor were selected by purposive sampling method. Based on the motto "Cinema can build a nation consciousness," it is aimed to trace the background of nationalism narrative in Turkish cinema. In this context, the assumptions of nationalism narrative is the main axis in historical film series portrayed by Cüneyt Arkin and religious and sacred figures are used to support nationalism ideology in historical film series with Cüneyt Arkin are tested. © 2023, IGI Global. All rights reserved.